Struktur Gerak Tari Lurah Kincia Di Sanggar Tari Lurah Kincia Nagari Situjuah Batua Kecamatan Situjuah Limo Nagari Kabupaten 50 Kota - Muttiah Razki Judenta; Susmiarti Susmiarti (SENDRATASIK UNP, 2020)
This study aims to describe and analyze the structure of the dance movement of Lurah Kincia dance in Situjuah Batua village, Situjuah Limo Nagari district, 50 Kota regency. This study belongs to a qualitative research using analytical descriptive method. The data used in this study were primary and secondary data. The main instrument used was the researcher itself and was assisted by supporting instruments such as writing instruments, cameras, and flash drives. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by collecting the data, describing the data, analyzing the data, and making conclusions. The results showthat the movement structure of Lurah Kincia dance has basic elements related to the attitude and movement of the body parts starting from the head, body, hands, and feet. From the relationship system between those elements, it produces motive forms in the form of turn taking, and are related to each other like a chain.The hierarchical grammatical relationship system contained in Lurah Kincia Dance consists of 37 motifs, 6 phrases, 4 sentences, and 1 cluster. Lurah Kincia dance belongs to a syntagmatic relationship system. It is a system whose relationship is like a chain and cannot be separated or exchanged between one another.